Companion of the 2020 ACM/IEEE International Conference on Human-Robot Interaction 2020
DOI: 10.1145/3371382.3378260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Handshake Turing Test for anthropomorphic Robots

Abstract: Handshakes are fundamental and common greeting and parting gestures among humans. They are important in shaping first impressions as people tend to associate character traits with a person's handshake. To widen the social acceptability of robots and make a lasting first impression, a good handshaking ability is an important skill for social robots. Therefore, to test the human-likeness of a robot handshake, we propose an initial Turing-like test, primarily for the hardware interface to future AI agents. We eva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…This can be seen in [25,87] where even though a human was controlling the robot having a rod-like end effector, this mode of shaking only got a human-likeness score of 6.8\10 by the participants. Even sophisticated mech-anisms, like the Android robot used in [78] which has a soft skin-like layer and heated palms, are still easily distinguished from a human's hand. One workaround could be to use sensing gloves, like by Orefice et al [61], which could help bridge the gap between a sophisticated interface and social robots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be seen in [25,87] where even though a human was controlling the robot having a rod-like end effector, this mode of shaking only got a human-likeness score of 6.8\10 by the participants. Even sophisticated mech-anisms, like the Android robot used in [78] which has a soft skin-like layer and heated palms, are still easily distinguished from a human's hand. One workaround could be to use sensing gloves, like by Orefice et al [61], which could help bridge the gap between a sophisticated interface and social robots.…”
Section: Discussionmentioning
confidence: 99%
“…Stock-Homburg et al [78] study whether a realistic android robot, that is modelled after a human, with soft silicone skin and pneumatically controlled joints can pass a hardware version of the Turing test. They have 15 participants blindfolded who have to interact with a human and the robot with their hand stretched out twice in a random order, leading to a total of 4 trials each.…”
Section: Human-likeness Of Robotic Handshakesmentioning
confidence: 99%
“…Of that dataset, 5/12 explained that the movement and direction and eye contact interaction made the RHR appear lifelike, and 2/12 suggested that Euclid made eye contact with them more frequently, which made for a greater authentic HRI [65]. Four out The HRI experiment consisted of 20 participants and was based on similar HRI studies [63,64]. Test subjects were recruited from the university with core modules in fields relating to computing and AI, including computer programming, application design and AI games programming.…”
Section: Hri Test Results and Analysismentioning
confidence: 99%
“…To minimise aesthetic differences, both the robotic and acrylic eyes employed the same iris image, and test subjects were not informed about the dilating robotic eye system before the experiment to minimise influential factors. The HRI experiment consisted of 20 participants and was based on similar HRI studies [63][64]. Test subjects were recruited from the university with core modules in fields relating to computing and AI, including computer programming, application design and AI games programming.…”
Section: Human-robot Interaction Experimentsmentioning
confidence: 99%
“…Researchers also investigated how a robot's body parts are essential to convey emotions by people/robots [41,42]. Other studies have focused on human touch interaction cues such as handshaking, describing its phases and analyzing both before-touch and after-touch actions [43], and defining methods for evaluating the human likeness of a robot handshake using a Turing-like test [44].…”
Section: Touch In Human-robot Interactionmentioning
confidence: 99%